Magnetic Doping Induced Strong Circularly Polarized Light Emission and Detection in 2D Layered Halide Perovskite. Issue 13 (1st May 2022) - Liu, Ying; Jiang, Ying; Xu, Zheyuan; Li, Lihui; Zhang, Danliang; Zheng, Weihao; Liang, Delang; Zheng, Biyuan; Liu, Huawei; Sun, Xingxia; Zhu, Chenguang; Lin, Lu; et al.
Abstract: The generation, manipulation, and detection of polarized light are the foundations of spin optoelectronics. Polarized light has a wide range of applications in new‐generation information transmission, storage, and quantum communications. Hybrid organic–inorganic halide perovskites have attracted extensive attention recently because of their strong spin–orbit coupling, Rashba splitting, spin‐dependent optical selection, and have been regarded as promising candidates for application in spin optoelectronic devices. Herein, the authors report the successful synthesis of 2D layered lead halide perovskites (PEA)2 PbI4 (PEI) doped with magnetic metal Co 2+ and the observation of strong circularly polarized photoluminescence and photoresponse. The introduction of magnetic metals in perovskites can induce an analogous Zeeman effect in the system, which can increase its energy degeneracy, giving rise to an imbalanced population of electronic spin states, thereby enhancing the spin polarization in doped samples. Thus, a maximum circularly polarized PL of 35% is observed at room temperature. Moreover, the achieved Co 2+ ‐doped (PEA)2 PbI4 also exhibits a selective photoresponse with circularly polarized light (CPL) emission, and an outstanding anisotropy factor of 0.41 for photocurrent is achieved. The experimental results lay the foundation for the controlled synthesis of magnetically doped perovskites as well as applications for direct CPL detection in spin optoelectronics. Abstract : Magnetic metal Co is successfully introduced into 2D layered halide perovskite by solution method. It is found that doped perovskite has excellent circularly polarized light (CPL) emission characteristics with left handed and right handed circularly polarized light excitation. Moreover, CPL detectors with good selectivity are demonstrated based on the as‐synthesized doped perovskites.